IT-BASED SERVICE DI PERGURUAN TINGGI (DAMPAK TERHADAP KEPUASAN DAN LOYALITAS) - Yohan Wismantoro (Semantik, 2011)
This study explores the impact of information technology (IT) on service quality in the higher education sector. It proposes a service quality model that links customer perceived IT- based service options to traditional service dimensions as measured by SERVQUAL in the context of customer perceived service quality and customer satisfaction. The model also incorporates several variables affecting customers’ perceptions of IT-based services, and was tested by a structural equation modeling approach using sample data collected from higher education customers. The results indicate that IT-based services have a directimpact on the SERVQUAL dimensions and an indirect impact on customer perceived service quality andcustomer satisfaction. The analyses also show that customers’ evaluations of IT-based services are affected by their preference towards experiences in using IT-based services.Keywords : Information technology, Service qualit,y, IT-based service